O Jornalismo de solução e a produção de um Jornalismo engajador - Gerevini, Isadora Dezorzi (2020)
This article aims to investigate whether the Cidades e Soluções program, broadcast by GloboNews, fits into the category of Solution Journalism (JS), based on the concepts proposed by the Solutions Journalism Network (2020), an organization specialized in producing and disseminating the culture of Solution Journalism. In addition to the Solutions Journalism Network, the article was based on research by Wenzel, Gerson and Moreno (2016) on JS's news production. Through bibliographical research, he searched the origins of Solution Journalism in some old currents, such as Journalism for Peace, described by Johan Galtung (1970) and Civic Journalism born in the United States (1980), to understand what points make them similar and what sets them apart. For the analysis, four editions of the Cidades e Soluções program were chosen, available free of charge on GloboNews' online platform, following the methodology that consisted of a content analysis, through which it was possible to carry out a quantitative and qualitative analysis, gleaning numbers and the content more clearly. From the results of the analysis, it was possible to conclude that the Cidades e Soluções program falls into the category of Solution Journalism, as the four editions evaluated contain the characteristics defined by the Solutions Journalism Network.